Capital gains tax in South Africa - Calson, Mark Kenneth (Centre for Law and Society, 2026)
Albert Einstein once said that the "hardest thing in the world to understand is the income tax"'. It is thus most appropriate that Capital Gains Tax ("CGT") has not been introduced into South African law as a separate tax but has rather been added to the Income Tax Act 58 of 1962 ("the Act") by means of an Eighth Schedule ("the Schedule"), with the effect that the levying, collection and administration of CGT al I take place in terms of the Act